Interlegality of Marriage Law: Tracing the Dynamics of Sumbong Marriages Practices in Jambi - Puspita, Mega; Umami, Khairul (Program Studi Hukum Keluarga Islam, 2024)
This article departs from the interlegality of marriage laws in Jambi society today, which discusses sumbong marriages. Sumbong marriage itself is a marriage that is legal according to religion, state, and custom. However, the ability to marry sumbong itself is considered valid by carrying out a customary settlement first, which was initially prohibited by customary law. The prohibition on marriage in Indonesia is contained in Article 8 of Law Number 1 of 1974 concerning Marriage and Article 39 of the Compilation of Islamic Law. Departing from this phenomenon, the author tries to examine the writing, which includes the implementation of marriage law in the Jambi community, the legal pluralism of the Jambi community, and the interlegality of customary, religious and state law in the marriage law of the Jambi community. The type of research carried out by the author is field research (Field Research) with qualitative methods. The nature of this research is analytical descriptive research. The approach used by the authors is a sociological empirical approach with interlegality. The author's findings clearly show that legal interactions in this tradition involve interactions between several laws, including religious, state, and customary laws used in sumbong marriage practices. By applying the legal interlegality theory approach, customary law, state law, and religious law become one unit. The concept of interlegality is found in adopting the values contained in the sumbong marriage tradition, whether based on state law, Islamic law, or Jambi customary law. This adoption process is based on the characteristics of the Jambi community's legal identity and its social environment, which is still steeped in customs, and the community also upholds the norms that apply in society and adheres firmly to